Aurora B kinase controls the separation of centromeric and telomeric heterochromatin. (3rd March 2016) - Gachet, Yannick; Reyes, Celine; Tournier, Sylvie
ABSTRACT: The segregation of chromosomes is coordinated at multiple levels to prevent chromosome loss, a phenotype frequently observed in cancers. We recently described an essential role for telomeres in the physical separation of chromosomes and identified Aurora B kinase as a double agent involved in the separation of centromeric and telomeric heterochromatin.